Inclusion and Literacy, Strategies for the Future of Islamic Finance - Samud, Samud; Shadiq, Teuku Fajar; Hasanah, Hani (PT. Hafasy Dwi Nawasena, 2025)
Islamic finance is one of the sectors with great potential in supporting global economic growth, especially in countries with a Muslim majority population such as Indonesia. However, the development of this sector still faces challenges, especially the low level of Islamic financial literacy and inclusion. Islamic financial literacy is related to the public's understanding of the principles, products, and benefits of Islamic finance, while inclusion reflects the extent to which the public has access to Islamic financial services. The purpose of this study is to discuss strategies that can be applied to improve Islamic financial literacy and inclusion, including through community-based education, digitalization of financial services, increasing product innovation, and strengthening supporting policies. The methodology used is a descriptive qualitative approach. This approach was chosen because it provides space to gain a deep understanding of the phenomenon being studied, namely the role of Islamic financial literacy and inclusion. The results of the discussion show that synergy between the government, Islamic financial institutions, and the community is needed to overcome existing obstacles. With the right approach, Islamic finance can not only be an alternative, but also an inclusive and sustainable financial solution, and contribute to national economic development.